2002
DOI: 10.1038/sj.gene.6363854
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular basis of thimerosal-induced apoptosis in T cells: a major role of mitochondrial pathway

Abstract: The major source of thimerosal (ethyl mercury thiosalicylate) . Thimerosal and not thiosalcylic acid (nonmercury component of thimerosal), in a concentration-dependent manner, induced apoptosis in T cells as determined by TUNEL and propidium iodide assays, suggesting a role of mercury in T cell apoptosis. Apoptosis was associated with depolarization of mitochondrial membrane, release of cytochrome c and apoptosis inducing factor (AIF) from the mitochondria, and activation of caspase-9 and caspase-3, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 57 publications
7
36
0
1
Order By: Relevance
“…Thus, the toxicity of thimerosal in the body may depend upon the concentrations of metal ions that provide either additive toxicity or protective effects on PI3-kinase signaling. Thimerosal has been reported to activate apoptosis in lymphocytes 62 and in cultured human cortical neurons, 63 consistent with the inhibition of the PI3-kinase signaling pathway.…”
Section: Igf-1 and Dopamine Regulate Methionine Synthase M Waly Et Almentioning
confidence: 71%
“…Thus, the toxicity of thimerosal in the body may depend upon the concentrations of metal ions that provide either additive toxicity or protective effects on PI3-kinase signaling. Thimerosal has been reported to activate apoptosis in lymphocytes 62 and in cultured human cortical neurons, 63 consistent with the inhibition of the PI3-kinase signaling pathway.…”
Section: Igf-1 and Dopamine Regulate Methionine Synthase M Waly Et Almentioning
confidence: 71%
“…A recent in vitro study of Thimerosal immunotoxicity using immortalized Jurkat T cells demonstrated an increase in reactive oxygen species and a decrease in intracellular glutathione with increasing concentrations of Thimerosal (Makani et al, 2002). Thimerosal, but not thiosalacylic acid (the non-mercury component of Thimerosal), induced apoptotic cell death in T cells in a concentration-dependent manner as evidenced by mitochondrial release of cytochrome c, apoptosis activating factor, and activation of caspases 9 and 3.…”
Section: Discussionmentioning
confidence: 98%
“…We envisaged that one such redox alteration may be the induction of cell death by apoptosis. 17,18 To test this idea we used both thimerosal 19 and hydrogen peroxide 20 as pro-apoptotic treatments to induce cell death, and monitored induction of MHC class I dimers by immunoblotting of cell lysates with HC10. Jesthom cells incubated with a range of thimerosal (1-5 lM) and hydrogen peroxide (0Á125-1 mM) concentrations showed significant MHC class I dimer formation (Fig.…”
Section: Hydrogen Peroxide and Thimerosal-induced Cell Death Induces mentioning
confidence: 99%